2016
DOI: 10.3233/jhd-150182
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Iron Supplementation Induces Striatal Atrophy in Female YAC128 Huntington’s Disease Mice

Abstract: BackgroundDysregulation of iron homeostasis is implicated in the pathogenesis of Huntington’s disease. We have previously shown that increased iron intake in R6/2 HD neonatal mice, but not adult R6/2 HD mice potentiates disease outcomes at 12-weeks of age corresponding to advanced HD [Redox Biol. 2015;4 : 363–74]. However, whether these findings extend to other HD models is unknown. In particular, it is unclear if increased neonatal iron intake can promote neurodegeneration in mouse HD models where disease ons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
2

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(40 citation statements)
references
References 39 publications
7
33
0
Order By: Relevance
“…NIS in R6/2 and YAC128 HD mouse models exacerbates neurodegeneration (Berggren et al, 2015, Berggren et al, 2016. Consistent with this, both N171--82Q HD mice (F (1,61) = 77.70, p < 0.001) and NIS (F (1,61) = 4.28, p = 0.0428) significantly decreased brain weights ( Fig.…”
Section: Neonatal Iron Supplementation Exacerbates Neurodegeneration supporting
confidence: 79%
See 1 more Smart Citation
“…NIS in R6/2 and YAC128 HD mouse models exacerbates neurodegeneration (Berggren et al, 2015, Berggren et al, 2016. Consistent with this, both N171--82Q HD mice (F (1,61) = 77.70, p < 0.001) and NIS (F (1,61) = 4.28, p = 0.0428) significantly decreased brain weights ( Fig.…”
Section: Neonatal Iron Supplementation Exacerbates Neurodegeneration supporting
confidence: 79%
“…Recommended daily allowances for iron have been developed to prevent iron deficiency, and upper limits were established to avoid short--term adverse effects (Micronutrients, 2001); however, long--term consequences of iron supplementation are not understood (Agrawal et al, 2017). We have previously shown that NIS in R6/2 and YAC128 mouse models of HD exacerbates disease progression (Berggren et al, 2015, Berggren et al, 2016. We have additionally shown that NIS promotes markers of mitochondrial dysfunction in R6/2 mice (Agrawal et al, 2018), although the cell--specific mechanisms by which NIS promotes HD in mice are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…They develop striatal and neocortical degeneration, as occurs in human HD [40]. WT and YAC128 HD mice (Jackson Labs) were maintained as described [41]. Mice were housed in OptiMice cages (Animal Care Systems) with 4--5 per cage and one genotype/treatment per cage [39].…”
Section: Mouse Husbandry and Breedingmentioning
confidence: 99%
“…Performance on the rotarod was completed as described [41]. Neurofilament light chain ELISA Neurofilament light chain (NFL) was measured in plasma at 8 and 12 months of age.…”
Section: Mouse Rotarodmentioning
confidence: 99%
See 1 more Smart Citation